Pelatihan Implementasi Perencanaan Keuangan Terhadap Efektivitas Pengelolaan Keuangan - Hendri Gunawan; Vega Anismadiyah; Vidya Amalia (Universitas Pamulang, 2023)
Financial planning is an important aspect that must be implemented by everyone toachieve good financial conditions faster, so financial planning is needed. Financial planning isused as a strategy to achieve life goals. Careful financial management is very important tomake our lives better now and in the future. Doing financial planning allows us to understandhow each financial decision will affect other areas of the overall financial condition. When welook at our overall financial condition, we can develop both short-term and long-term impactson life goals. We can more easily adapt to life changes and feel more confident with a healthyfinancial condition.Mentioned that we have strong financial quality and financially independentconditions in the future is a good intention to have. However, in realizing this dream, intentionalone is enough. We must start to find and find the right way to manage finances. It should berealized that everyone's way of managing finances will be different. But with the same goal, wecan also take the essence or some tips and tricks in managing finances that can be adapted toour personality, needs, and lifestyle. Finding ways to manage finances that suit us needs to bedone early. Since we were young and productive. Therefore, managing finances properly andhealthily is needed so that our future can be well maintained and it will make it easier for us tomeet all needs, whether planned or planned. We also need to pay attention to finding ways tomanage finances from a young age, because finding ways or methods that suit things is easy